PENGARUH INDEPENDENSI, PENGALAMAN, DUE PROFESSIONAL CARE DAN AKUNTABILITAS TERHADAP KUALITAS AUDIT (STUDI EMPIRIS TERHADAP AUDITOR KAP KOTA MEDAN): PENGARUH INDEPENDENSI, PENGALAMAN, DUE PROFESSIONAL CARE DAN AKUNTABILITAS TERHADAP KUALITAS AUDIT (STUDI EMPIRIS TERHADAP AUDITOR KAP KOTA MEDAN) - Afrizar Pane; Surya Kelana Putra; Surya Misauri; Melisa Melisa; Agnes Silvya; Febrianti Nababan (Jurnal Mantik, 2019)
This research aims to determine: (1) Effect of independence on audit quality, (2) Effect of experience on audit quality, (3) Effect of due professional care on audit quality, (4) Effect of accountability on audit quality. This type of research is descriptive research. The population in this study were all auditors working at the Public Accountant Office in the city of Medan. The type of sampling technique used in this study is using purposive sampling. The data source in this study is primary data. Data collection techniques using questionnaires. Data analysis techniques used multiple linear regression analysis with the help of SPSS version 2.3. The results showed that: (1) The effect of independence had a significant effect, (2) The effect of experience had a significant effect, (3) The effect of due professional care had a significant effect, (4) The effect of accountability had a significant effect on audit quality. Suggestions in this study are: to the auditor of the Public Accountant Office is the auditor must have a neutral attitude in carrying out their duties, increase knowledge and experience so that audit activities can run well, and have a careful attitude in providing income and have professional responsibilities in carrying out his job as an audit to be able to produce a quality and accountable audit.